Про досвід відтворення звукової інформації з раритетних носіїв і введення її до наукового обігу - Косяк, І.В.; Єгупова, Л.І. (Реєстрація, зберігання і обробка даних, 2017)
Розглянуто сучасний стан проблеми збереження та відновлення звукової культурної спадщини першої половини XX сторіччя. Здійснено відтворення та оцифровування звукової інформації, що зберігається на раритетних носіях. Проведено обробку та реконструкцію звукових сигналів записів фонограм. Рассмотрено современное состояние проблемы сохранения и восстановления звукового культурного наследия первой половины ХХ столетия. Осуществлено воспроизведение и оцифровка звуковой информации, хранящейся на раритетных носителях. Проведена обработка и реконструкция звуковых сигналов записей фонограмм. It is a great merit of Edison in that we now have an opportunity to hear the voices of famous peop-le of the beginning of the 20th century. Collections of records on cylinders allowed to retain the language and musical traditions of different cultures.Today, this material became invaluable. Unfortunately, after many listenings a wax layer of cylinders becoms more and more damaged. There is a great need for high-quality transfer of cylinders to preserve spiritual heritage for future generations. The current state of the problem of sound preservation and restoration of cultural heritage of the first half of the twentieth century is considered. The restoration and digitization of audio information stored on the rarity record carriers are carried out. Records made on phonograph cylinders being characterized by high level of noise which are bound up with mechanical damage to the surface, sticking of dust, destruction of the wax cylinder surface by microorganisms. A processing and reconstruction sound signal recordings of phonograms have been carried out.